Gender-Based Violence and Global Capitalism: Everyday experiences of female laborers in the fast fashion garment industry - Febrilly, Vanesha; Siscawati, Mia (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2023)
The garment industry is an industrial sector that recruits more female laborers. However, female laborers in the garment industry often experience various forms of injustice and acts of violence, such as low wages, gender discrimination or high workloads. Various forms of injustice and violence must be studied continuously, considering that this industry is still rapidly growing globally. The emergence of the fast fashion trend encourages the expansion of the garment industry, which can potentially eternalize injustice and violence against female laborers. Female garment laborers bear a substantial role in the production sector, starting from preparing materials, cutting materials, sewing, ironing, and playing various roles as helpers in various production processes. This paper examines daily experiences of injustice and violence experienced by several female garment laborers from one of the garment factories in Jakarta. Adopting the theoretical approach of feminist everyday political economy, this paper analyzes those experiences that reflect miscellaneous structural and cultural gender violence heavily influenced by global capitalism.